Le front oriental de Lille - Étienne Poncelet (In Situ)
The east wall, at Lille, fortified during the period of Spanish occupation, extends from the Porte d'Eau de la Basse-Deûle to the Saint-Sauveur fort. Its curtain walls emerge today in a landscape of ring roads and railway territories. The issue today is to profit from these historic walls in order to make some sense of the urban chaos and to reinstate some urban continuity in the city-centre walkways. Although they are not as well known as the western wall of this major fortified city, these former military properties are an exciting opportunity for tomorrow's town-planners, as the operations already underway at the Porte de Gand et de la Basse Deûle suggest.